Implementation of fuzzy logic to measure supply chain agility - Mehdi Karimimalayer; Nizaroyani Saibani (Universitas Ahmad Dahlan, 2016)
In our age of perennial changing environment, supply chain agility is a crucial factor having a great impact on the company's competitiveness. For transforming supply chain into an agile supply chain, first it is necessary to comprehend the meaning of agile supply chain, since agility has wide range of meanings and various dimensions which covers different aspects of an organization. Generally, however, there have been many researches on agility, proportionally; the concept of agility in supply chain has not been much surveyed. The circumstance unveils the necessity of a technique to measure the supply chain agility. The purpose of the article is to propose a technique, using fuzzy logic which supply chain agility be measured.